Comparative Study of Classical Greek Ethics and Islamic Ethics - Endrika Widdia Putri (Ulumuna, 2019)
The notion that Islamic ethics originate from Classical Greek ethics needs examination. It is true that Muslim thinkers or scholars who wrote works on ethics were influenced by classical Greek philosophers. However, there are strong fundamental characters that distinguish Islamic ethics from Greek ethics. This study aims to highlight these differences and critically shows that such differences come from philosophical and ethical principles. Base on a comparative study of Muslims and Greek philosophers, this study shows that in substance, the style of Islamic ethics is very different from Classical Greek ethics. While Classical Greek ethics reveals its fundamental character of atheism, focusing on human relationship while releasing faith in its discussion, Islamic ethics tends to expose the characters of theism. Its discourse reaches the level of spirituality that covers not only inter-human relationships but also the relationship between humans and God. It also refers to the scriptural sources such as the Qur'an and Hadith and Islamic ethics related to faith. Nevertheless, both of them have commonalities in the relationship between ethics and happiness, which become the highest goal of ethics in both traditions.